Impact of the karnofsky performance status on survival and its dynamics during the terminal year of peritoneal dialysis patients - Modesto, Ana Paula; Usvyat, Len; Calice-Silva, Viviane; Spigolon, Dandara Novakowski; Figueiredo, Ana Elizabeth; de Moraes, Thyago Proença; Olandoski, Marcia; Shimakura, Silvia Emiko; Barreti, Pasqual; Kotanko, Peter; Pecoits-Filho, Roberto (SAGE Publications, 2018)
Background: Simple and low-cost tools to monitor the risk profile of patients on peritoneal dialysis (PD) at high risk of complications and mortality are scarce. One of the tools available to monitor the variation in vitality and dependence levels is the Karnofsky performance status (KPS). This study analyzed the average trends and variation of KPS during the 12 months before death and its independent value in predicting patients’ survival. Methods: The data were compiled from the BRAZPD II multi-center study, performed in Brazil between 2004 and 2011. For the analysis of KPS dynamics, we included patients with at least 12 months of follow-up on PD and who had a fatal event during the follow-up. The following covariables were evaluated: age, gender, ethnicity, educational level, and presence of diabetes. We used the linear regression model to present the results: the log (time) before death was represented by the regression variable and KPS was the response. We also analyzed the independent impact of baseline KPS on patients’ survival. Results: From the population of 9,905 patients enrolled in the BRAZPD study, 4,133 survived 12 months on PD and were included in the analysis. There was a gradual decline in the KPS scores, which accelerated in the last 2 months before death. These changes were similar irrespective of age, race, family income, gender, diabetes, PD modality, and education level. We observed 989 fatal events in this population during the observation period, and the KPS score was identified as an independent predictor for mortality in this cohort. Conclusions: This study demonstrates for the first time the dynamics of KPS before death in PD patients, indicating a progressive and accelerated decline of KPS in the 12 months before patients died. In addition, KPS was an independent predictor of mortality in this population.
Keywords: Karnofsky performance status; Peritoneal dialysis